2021
DOI: 10.3390/nano11061467
|View full text |Cite
|
Sign up to set email alerts
|

Nanotechnological Applications Based on Bacterial Encapsulins

Abstract: Encapsulins are proteinaceous nanocontainers, constructed by a single species of shell protein that self-assemble into 20–40 nm icosahedral particles. Encapsulins are structurally similar to the capsids of viruses of the HK97-like lineage, to which they are evolutionarily related. Nearly all these nanocontainers encase a single oligomeric protein that defines the physiological role of the complex, although a few encapsulate several activities within a single particle. Encapsulins are abundant in bacteria and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 133 publications
(323 reference statements)
0
23
0
1
Order By: Relevance
“…7 During the last years, activity of various (non-) natural guest enzymes inside these capsids was investigated. [8][9][10][11][12] Figure 1: The present research work is highlighted as a merging concept of several previously reported approaches. Moreover, future perspectives in ArM and nanoreactor research are shown.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…7 During the last years, activity of various (non-) natural guest enzymes inside these capsids was investigated. [8][9][10][11][12] Figure 1: The present research work is highlighted as a merging concept of several previously reported approaches. Moreover, future perspectives in ArM and nanoreactor research are shown.…”
Section: Introductionmentioning
confidence: 65%
“…The herein presented nanoreactor is the first report of a two-step, dual-functional ArM driven, fully bioorthogonal reaction cascade inside a proteinaceous capsid opening up exciting possibilities in the field of designing artificial organelles with compartmentalized reaction pathways. 8,9,[48][49][50] The novel gold-phosphine complex AuB is established herein for both bioorthogonal catalysis in aqueous solutions and as an avidin cofactor. With a TON above 400 its catalytic activity is comparable to the previously described gold-NHC complexes.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, with future engineering applications in mind, we chose to focus our bioinformatic search for acid-tolerant shells on Family 1. 3,4,27,28 Further arguments for focusing on Family 1 are that the widespread DyP encapsulins found in Family 1 are known to optimally function under acidic conditions 29 while a variety of Family 1 systems encoded by acid-tolerant and acidophilic bacteria have already been previously identified. 4 As acid-tolerant proteins generally possess a low calculated isoelectric point (pI) caused by a large number of surface-exposed negatively charged residues, 22,25,26,30 it was hypothesized that encapsulins with a low pI may exhibit increased acid tolerance.…”
Section: Resultsmentioning
confidence: 99%
“…The in vitro structural and functional studies along with the in vivo work have been fruitful for understanding nanocompartment biology and this kind of work will continue to yield insights when applied to other nanocompartment complexes of unknown function. These studies will also lead to new insights into applications of bacterial nanocompartments in therapeutics and research ( Gabashvili et al, 2020 , Rodríguez et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%